Insights into local health and wellbeing policy process in Australia - Lilly, Kara; Hallett, Jonathan; Robinson, Suzanne; Selvey, Linda A. (OXFORD UNIV PRESS, 2020)
To investigate factors that enable or challenge the initiation and actioning of health and wellbeing policy in Australian local governments using political science frameworks. An online survey was distributed to staff and elected members of Australian local governments. The survey sought responses to a range of variables as informed by political science frameworks. Data were analysed using descriptive statistics and results were compared between local governments of different geographical sizes and locations using Kruskal-Wallis non-parametric testing. There were 1825 survey responses, including 243 CEOs, representing 45% of Australian local governments. Enablers for local government policy initiation and action included the high priority given to health and wellbeing (44%), local leadership (56%) and an organizational (70%) and personal obligation (68%) to the community to act. Less true is a favourable legislative environment (33%), leadership from higher levels of government (29%) and sufficient financial capacity (22%). Cities are better positioned to initiate and action health policy, regardless of the broader legislative environment. Health and wellbeing is a high priority for Australian local governments, despite lack of funding and limited lobbying and support from other sectors and higher levels of government. The insights from political science frameworks assist to understand the policy process, including the interrelatedness of enablers and challenges to initiating and actioning health and wellbeing policy. Further understanding the policy drivers would support practitioners and researchers advocating to influence local health and wellbeing policy.